Math, asked by leenachaudhari4, 10 months ago

(3k+1)x+3y = 2 and (K^2+1)x +(K-2)y-5=0
find the value of k​

Answers

Answered by aryanbhadoriya411
1

Answer:

Step-by-step explanation:

The given system of equations is

(3k+1)x+3y−2=0

(k  

2

+1)x+(k−2)y−5=0

This is of the form a  

1

​  

x+b  

1

​  

y+c  

1

​  

=0

a  

2

​  

x+b  

2

​  

y+c  

2

​  

=0,

where, a  

1

​  

=3k+1,b  

1

​  

=3,c  

1

​  

=−2  

and a  

1

​  

=k  

2

+1,b  

2

​  

=k−2,c  

2

​  

=−5

For no solution, we must have

a  

2

​  

 

a  

1

​  

 

​  

=  

b  

2

​  

 

b  

1

​  

 

​  

 

​  

=  

c  

2

​  

 

c  

1

​  

 

​  

 

The given system of equations will have no solution, if

k  

2

+1

3k+1

​  

=  

k−2

3

​  

 

​  

=  

−5

−2

​  

 

⇒  

k  

2

+1

3k+1

​  

=  

k−2

3

​  

 and  

k−2

3

​  

 

​  

=  

5

2

​  

 

Now,  

k  

2

+1

3k+1

​  

=  

k−2

3

​  

 

⇒(3k+1)(k−2)=3(k  

2

+1)

⇒3k  

2

−5k−2=3k  

2

+3

⇒−5k−2=3

⇒−5k=5

⇒k=−1

Clearly,  

k−2

3

​  

 

​  

=  

5

2

​  

 for k=−1

Hence, the given system of equations will have no solution for k=−1.

Answered by HiguysIamgirl
0

Answer: -1

Step-by-step explanation:

The given system of equations is

(3k+1)x+3y−2=0

(k  

2

+1)x+(k−2)y−5=0

This is of the form a  

1

x+b  

1

y+c  

1

=0

a  

2

x+b  

2

y+c  

2

=0,

where, a  

1

=3k+1,b  

1

=3,c  

1

=−2  

and a  

1

=k  

2

+1,b  

2

=k−2,c  

2

=−5

For no solution, we must have

a  

2

 

a  

1

 

=  

b  

2

 

b  

1

 

 

=  

c  

2

 

c  

1

 

 

The given system of equations will have no solution, if

k  

2

+1

3k+1

=  

k−2

3

 

=  

−5

−2

 

⇒  

k  

2

+1

3k+1

=  

k−2

3

 and  

k−2

3

 

=  

5

2

 

Now,  

k  

2

+1

3k+1

=  

k−2

3

 

⇒(3k+1)(k−2)=3(k  

2

+1)

⇒3k  

2

−5k−2=3k  

2

+3

⇒−5k−2=3

⇒−5k=5

⇒k=−1

Clearly,  

k−2

3

 

=  

5

2

 for k=−1

Hence, the given system of equations will have no solution for k=−1.

Similar questions